Noisy commitments: the impact of information accuracy on efficiency - Eyal Ert; Andreas Nicklisch (Max Planck Institute for Research on Collective Goods, 2006)
We report an experiment designed to test the influence of noisy commitments on efficiency in a simple bargaining game. We investigate two different levels of commitment reliability in a variant of the peasant-dictator game. Theoretical analysis suggests that the reliability of commitments in this game does not affect efficiency. We find that accurate commitments promote efficiency, as expected by game theory. However, noisy commitments are found to impair efficiency. We explain this effect by the differences between incentives off the equilibrium path under conditions of accurate commitments and noisy commitments. This difference changes the game structure and in the current game facilitates more random responses.
Keywords: C7; C91; L15; 330; Commitments; efficiency; experimental economics; information; trust